Pentahelix Collaboration in Developing the Tourist Attractions of Mali Beach, Alor Regency - Koby, Antonius (Faculty of Economics and Business, University of Mataram, 2025)
Tourism is an important sector in contributing to increasing income for regions and communities if managed with a good approach. Pentahelix collaboration is an approach to tourism development that involves the government, community, academics, business actors, and the media. Mali beach tourism has the potential for the main attraction of the dugong species, but has not attracted significant tourist visits. Data from 2023 showed that the percentage of visits was only 1.42% of the average 4.54% of visits at the provincial level. The purpose of the study was to analyze the implementation of pentahelix collaboration in tourism development on the Mali Coast. The study was conducted based on previous research that showed that pentahelix collaboration is important in developing tourist attractions. Data collection used qualitative methods through interviews with representatives of pentahelix elements and tourists, observation, and documentation. The results of the study revealed that tourism development is dominated by the government, while other stakeholders are only complementary and coordinated in a forum for communication and joint decision-making. For this reason, it is necessary to explore and organize the implementation of pentahelix collaboration in order to increase tourist visits to the Mali Beach tourist attraction.